2021
DOI: 10.5539/ijms.v13n1p14
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Study of Factors Influencing Consumers’ Purchasing Behaviours in Shopping Malls

Abstract: Since a couple of years ago, the development of shopping malls is booming in the Klang Valley-Kuala Lumpur area in Malaysia. Motivating consumers for frequent visits to shopping complexes is imperative in order to run a successful shopping mall in such a competitive retail environment like the Klang Valley-Kuala Lumpur with over 100 shopping plazas. Getting knowledge of the elements attracting consumers to visit a shopping mall and make purchases is of greatest importance in order to achieve high profit return… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
0
0
Order By: Relevance
“…Secondly, our study proposed that the accessibility to and inside the malls had a significant impact on the minds of customers in terms of shaping their experience. These findings were consistent with previous studies [41,44] that found a significant positive relation between accessibility and shopping experience, and suggest that shopping centres should be accessible with only reasonable effort. This is particularly pivotal in the context of Dhaka City-a bustling city that is jampacked with traffic and possesses a shortage of transportation would appreciate the shopping mall located in the vicinity of the customers' workplaces and homes.…”
Section: Discussion and Implications For Managerssupporting
confidence: 92%
See 1 more Smart Citation
“…Secondly, our study proposed that the accessibility to and inside the malls had a significant impact on the minds of customers in terms of shaping their experience. These findings were consistent with previous studies [41,44] that found a significant positive relation between accessibility and shopping experience, and suggest that shopping centres should be accessible with only reasonable effort. This is particularly pivotal in the context of Dhaka City-a bustling city that is jampacked with traffic and possesses a shortage of transportation would appreciate the shopping mall located in the vicinity of the customers' workplaces and homes.…”
Section: Discussion and Implications For Managerssupporting
confidence: 92%
“…The authors of [43], in a bid to define one-stop shopping, stated that almost all the abstracts of shopping needs could be catered to in one particular centre, all at once. In another study on the determinants of consumers' purchasing behaviour, transportation and location-related factors were found to have the greatest impact on mall shoppers' purchase decisions [44]. Since consumers currently are more interested in taking multi-purpose visits to shopping malls [45], it is more likely that they will favour centres that facilitate one-stop solutions for shoppers.…”
Section: Accessibilitymentioning
confidence: 99%
“…Additionally, perceptions of mall convenience, including convenient location and parking facilities, positively affect shoppers' satisfaction levels, ultimately influencing their intention to visit and shop there [33,35]. Transportation and location-related factors were also found to significantly impact mall shoppers' purchase decisions in a study on the determinants of consumer purchasing behavior [38]. As consumers increasingly prioritize multi-purpose visits to shopping malls [39], centers offering shoppers one-stop solutions are more likely to be favored.…”
Section: Accessibilitymentioning
confidence: 99%
“…Man and Qiu [7], delved into the factors that influence consumer buying behaviors within shopping malls, identifying environmental, service-related, administrative, transportation, and location factors as key independent variables. The research framework was established through a comprehensive review of existing literature.…”
Section: Factors Influencing Customer Preferencesmentioning
confidence: 99%